Renal function in heart failure: a disparity between estimating function and predicting mortality risk. (July 2013) - Plischke, Max; Neuhold, Stephanie; Kohl, Maria; Heinze, Georg; Sunder‐Plassmann, Gere; Pacher, Richard; Hülsmann, Martin
<x xml:space="preserve">Abstract</x> Aims To compare the predictive value of estimated renal function calculated by the Chronic Kidney Disease Epidemiology Collaboration (eGFRCKD‐EPI), four‐variable Modification of Diet in Renal Disease (eGFRMDRD‐4), and Cockcroft–Gault [estimated creatinine clearance (eCcr)] equation in terms of all‐cause mortality in heart failure. Renal function is an important prognostic factor in heart failure. Established methods of estimating renal function are known to under‐/overestimate true function in certain settings. Methods and results A total of 800 systolic heart failure outpatients (mean age 57 ± 11.5 years, 82% male) were studied over a median follow‐up of 121 (Q1–Q3: 110–130) months. The highest systematic difference was seen between eCcr and eGFRMDRD‐4 [+12.33 points (mean), 95% limits of agreement –22.35 to 47.01; generalized kappa = 0.36]. eGFRMDRD‐4 and eGFRCKD‐EPI were the most similar [–4.16 points (mean), 95% limits of agreement –11.56 to 3.25; generalized kappa = 0.74]. Up to 35.4% of patients were reclassified into different estimated glomerular filtration rate (eGFR) categories when comparing eGFRCKD‐EPI with eCcr and eGFRMDRD‐4. eGFRCKD‐EPI performed marginally better in terms of predicting all‐cause mortality than eGFRMDRD‐4, as univariate areas under the time‐dependent receiver operating characteristic curves (AUC), marginal and partial proportions of explained variation (PEV), net reclassification improvement (NRI), and the integrated discrimination improvement (IDI) for 5 years of follow‐up were significantly higher for eGFRCKD‐EPI than for eGFRMDRD‐4. Conclusion In this cohort of heart failure patients, eGFRCKD‐EPI was marginally better in predicting all‐cause mortality than eGFRMDRD‐4. Estimated function differed widely between equations and is likely to have an effect on therapy choice.